2006
DOI: 10.2165/00002018-200629120-00005
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of Different Dosing Regimens of Bisphosphonates for the Treatment of Osteoporosis and Malignant Bone Disease

Abstract: Bisphosphonates are the primary pharmacological agents used for the management of osteoporosis and hypercalcaemia of malignant bone disease. The efficacy of these agents in these two conditions has been demonstrated in many well designed trials published over the past 2 decades. The variety of bisphosphonates currently available to us provides a wide range of tolerability and dosing profiles thus necessitating a thorough comparison of the most recent oral and intravenous bisphosphonates to differentiate the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 80 publications
1
39
0
1
Order By: Relevance
“…In addition, we have not included adverse effects with oral bisphosphonates. Although oral bisphosphonates are generally well tolerated, they are likely to be associated with upper gastrointestinal adverse events, [73] which may require additional costs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have not included adverse effects with oral bisphosphonates. Although oral bisphosphonates are generally well tolerated, they are likely to be associated with upper gastrointestinal adverse events, [73] which may require additional costs.…”
Section: Discussionmentioning
confidence: 99%
“…9 Risedronate and ibandronate seem to have a GI tolerability similar to that of alendronate. 9,10 Current evidence, as presented above, should be reassuring to practitioners and patients in that the use of oral bisphosphonates for treatment of osteoporosis does not increase the likelihood of upper GI adverse events on condition that the patients adhere to the rules of correct dosing and mode of intake of these drugs. With regard to upper GI tract safety, women were excluded from participating in the FIT study 5 if they had had upper GI tract bleeding within the past five years requiring hospitalization or transfusion; documented recurrent or recent ulcer disease (two episodes in the preceding five years or one episode in the preceding 12 months); experienced esophageal or gastric varices; or used medication daily for dyspepsia.…”
Section: Upper Gastrointestinal Tract Adverse Eventsmentioning
confidence: 99%
“…Fourteen reviews summarising evidence for AEs across studies in bisphosphonates were identified. [112][113][114][115][116][117][118][119][120][121][122][123][124][125] A summary of these reviews and their findings is presented in Table 48, Appendix 5.…”
Section: Systematic Review Evidence For Adverse Eventsmentioning
confidence: 99%
“…[112][113][114][115][116][117][118][119][120][121][122][123][124][125] One review considered any antresorptive therapy, 123 10 considered any bisphosphonate therapy 112,114,[117][118][119][120][121][122]124,125 and three reported on AEs associated with specific bisphosphonates (two in risedronic acid 113,115 and one in alendronic acid or risedronic acid 116 ). Four reviews included evidence from both observational studies and RCTs 112,116,117,125 and seven included only observational studies. [118][119][120][121][122][123][124] Five reviews reported on any AE, [112][113][114][115] whereas nine reported on specific AEs (four in jaw osteonecrosis, [117][118]…”
Section: Atrial Fibrillation Loke Et Almentioning
confidence: 99%
See 1 more Smart Citation